2012
DOI: 10.1111/jph.12051
|View full text |Cite
|
Sign up to set email alerts
|

Improved Resistance to Cucumber mosaic virus in Petunia Transformed with Non‐Cytotoxic Pokeweed Antiviral Protein Gene

Abstract: Petunia hybrida is an important ornamental plant that can be seriously affected by cucumber mosaic virus (CMV). Pokeweed antiviral protein (PAP), a ribosome‐inactivating protein, has been recognized as a broad spectrum virus inhibitory agent. Mutant PAP efficiently inhibited viral gene expression at both the translational and transcriptional levels without causing host cell toxicity. We have transferred the non‐cytotoxic pokeweed antiviral protein (mutant PAP) gene into petunia cells with Agrobacterium tumefac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…have been the most studied antiviral proteins in transgenic development, mainly PAP I, PAP II, PhRIP I, Pac-PAP, and PIP. The PAP has been successfully overexpressed in different transgenic plants, which lead to improved resistance against multiple plant viruses such as CMV, PLRV, PVX, PVY, TMV, and TuMV (Di & Tumer, 2005;Fu et al, 2000;Li et al, 2013;Lodge et al, 1993;Moon et al, 1994;Smirnov et al, 1997;Tumer et al, 1997;Zhang et al, 1999;Zhao et al, 2008;Zoubenko et al, 2000). Lodge et al (1993) introduced PAP into tobacco and potato plants which enabled transgenic plants to develop resistance to a broad-spectrum of plant viruses, and the resistance was also effective against both mechanically and aphid-transmitted viruses.…”
Section: Transgenic Plant Development With Antiviral Ripsmentioning
confidence: 99%
See 1 more Smart Citation
“…have been the most studied antiviral proteins in transgenic development, mainly PAP I, PAP II, PhRIP I, Pac-PAP, and PIP. The PAP has been successfully overexpressed in different transgenic plants, which lead to improved resistance against multiple plant viruses such as CMV, PLRV, PVX, PVY, TMV, and TuMV (Di & Tumer, 2005;Fu et al, 2000;Li et al, 2013;Lodge et al, 1993;Moon et al, 1994;Smirnov et al, 1997;Tumer et al, 1997;Zhang et al, 1999;Zhao et al, 2008;Zoubenko et al, 2000). Lodge et al (1993) introduced PAP into tobacco and potato plants which enabled transgenic plants to develop resistance to a broad-spectrum of plant viruses, and the resistance was also effective against both mechanically and aphid-transmitted viruses.…”
Section: Transgenic Plant Development With Antiviral Ripsmentioning
confidence: 99%
“…However, it has been reported that high levels of wild-type or variant PAP (PAPv) expression in transgenic plants was also toxic to plant cells (Lodge et al, 1993). The non-toxic PAP mutants (PAPc, PAPn) have also been efficiently expressed in transgenic plants and induced resistance to virus infections, but not toxic to plants harbouring the transgene (Li et al, 2013;Tumer et al, 1997;Zoubenko et al, 2000). The transgenic expression of PAP II in tobacco also exhibited broadspectrum resistance to PVX and TMV, as well as a fungal pathogen.…”
Section: Transgenic Plant Development With Antiviral Ripsmentioning
confidence: 99%
“…Removing a specific adenine base from the large ribosomal RNA, PAP acts as a ribosome inactivating protein. LI et al (2013) have transferred modified PAP gene into petunia cells with A. tumefaciens and obtained transgenic plants immune or highly resistant to Cucumber mosaic virus (CMV).…”
Section: Disease Resistancementioning
confidence: 99%